Oestrus synchronization for accelerated delivery of improved dairy genetics in Ethiopia: Results from action research and development interventions - Gizaw, Solomon; Tesfaye, Y.; Mekuriaw, Z.; Tadesse, M.; Hoekstra, Dirk; Gebremedhin, Berhanu; Tegegne, Azage (International Livestock Research Institute, 2016)
Oestrous synchronization is the manipulation of the oestrous cycle or induction of oestrus to bring a large percentage of a group of females cattle into oestrus at a short, predetermined time.